High opioid dose escalation to 100 and 200 mg per day in patients with long term opioid therapy: Sex difference - Zin, Che Suraya; Taufek, Nor Hidayah; Alias, Nor Elina; Meor Ahmad, Mazlila (2019)
Background It was reported that the risk of opioid overdose death increased with increasing opioid dose and little is known whether sex difference influences the risk of opioid dose escalation or overdose. Objective This study examined the relationship between sex difference and opioid dose escalation in patients with long term opioid therapy.